System Design and Implementation of Multiprobe Planar Near Field Antenna Measurements - Antonyan, Samvel
This article presents practical implementation of a novel multiprobe planar near-field range (PNFR) measurement system, utilizing a simplified mechanical setup with seven antipodal Vivaldi antennas serving as probes. The proposed system retains the design simplicity of existing configurations while enhancing measurement efficiency by reducing testing time. The antipodal Vivaldi antennas, known for their broadband capabilities, ensure precise and wideband near-field measurements. The developed setup is experimentally validated on a representative antenna under test (AUT) in the X-band frequency range, demonstrating its practical effectiveness and robustness in real-world applications. The results confirm the system’s ability to deliver high-resolution measurements, consistent with numerical simulations, thereby affirming its viability for advanced antenna testing and characterization.
Keywords: Physics